Tinjauan Variasi Diameter Kolom Kapur Terhadap Kuat Geser Tanah Lempung Lunak - Sari, Aian Nisa Permata, Anto Budi Listyawan, S.T, M.Sc, Agus Susanto, S.T, M.T (2016)
The various soil in some areas in Indonesia causes some damage to the infrastructure. Such as, roads cracked in Purwodadi, the floor surface was cracked and broken in Sragen, the building floor area collapsed in Boyolali, all of it due to the type of soil in those area is clay. One case of soft clay soil that has been investigated is on the Troketon Village, Pedan Sub-district, Klaten District, as who was done by Setiawan, A (2008) and Merdhiyanto, P (2015). Soft clay soil has a low bearing capacity and high develop shrinkage. With those soil conditions, it causes the roads cracked, the floor of the building collapsed, and the building walls cracked. To improve those soil condition, it is stabilized with chemical stabilization by using lime column. This study is focused on the variation of lime column diameter toward the soft clay soil shear strength. In this study using lime column diameter 10 cm, 15 cm and 20 cm. The results show that the stabilization with lime columns can improve the values of cohesion and inside friction angle soil. Stabilized soil with lime column, the biggest value of cohesion and inside friction angle is found on lime column 20 cm diameter, with cohesion value is 0.558 kg/cm2 from the original cohesion value is 0,142 kg/cm2, the value of inside friction angle is 6,099o of the value of inside friction angle is 1,809o and the shear strength increases up to 0.741 kg/cm2. The larger diameter of lime columns, so the values of cohesion, inside friction angle, and shear strength increase, but not able to improve the properties of soil plasticity. Thus stabilization with limes columns was able to improve the soil shear strength.